Assessment of Testamentary Capacity in Older Adults: Description and Initial Validation of a Standardized Interview Instrument. (22nd May 2022) - Martin, Roy C; Gerstenecker, Adam; Hebert, Katina; Triebel, Kristen; Marson, Daniel
Abstract: Objective: Testamentary capacity (TC) is a legal construct, which concerns a person's mental capacity to make or amend a will. Although expert clinicians are frequently asked to assess TC in forensic settings, there are few instruments and little empirical research to inform and guide their assessments. The present study describes the development and psychometric properties of a standardized assessment measure of TC (Testamentary Capacity Instrument-TCI), and investigates its reliability and validity. Methods: The TCI is an interview-based, psychometric measure, which assesses a testator's knowledge of four conceptual elements, which together comprise the legal basis for TC in the Anglo-American legal system: (1) what a will is, (2) nature and extent of assets/property, (3) possible heirs/claimants to property, and (4) plan to distribute assets to heirs after death. Cronbach's alpha and percentage exact agreement were used to examine TCI element reliabilities. Using independent samples t -tests, MANOVA and MANCOVA, we investigated validity by comparing TCI element performance of cognitively intact older adults ( n  = 22) and older adults with ad dementia ( n  = 20). Results: The TCI elements showed good internal consistency and good inter-rater reliability. The ad group performed significantly below the control group on all four TCI elements, with effect sizes exceeding 1.2, suggesting that the TCI has content and construct validity. Conclusions: Relative to cognitively intact older adults, older adults with ad dementia showed significant impairment on all four TCI conceptual elements. The TCI has promise as a standardized quantitative measure of TC to support clinical assessment of TC in forensic settings.